Bacillus pumilus Group Comparative Genomics: Toward Pangenome Features, Diversity, and Marine Environmental Adaptation - Fu, Xiaoteng; Gong, Linfeng; Liu, Yang; Lai, Qiliang; Li, Guangyu; Shao, Zongze (Frontiers in Microbiology, 2021)
Background: Members of the Bacillus pumilus group (abbreviated as the Bp group) are quite diverse and ubiquitous in marine environments, but little is known about correlation with their terrestrial counterparts. In this study, 16 marine strains that we had isolated before were sequenced and comparative genome analyses were performed with a total of 52 Bp group strains. The analyses included 20 marine isolates (which included the 16 new strains) and 32 terrestrial isolates, and their evolutionary relationships, differentiation, and environmental adaptation. Results: Phylogenomic analysis revealed that the marine Bp group strains were grouped into three species: B. pumilus, B. altitudinis and B. safensis. All the three share a common ancestor. However, members of B. altitudinis were observed to cluster independently, separating from the other two, thus diverging from the others. Consistent with the universal nature of genes involved in the functioning of the translational machinery, the genes related to translation were enriched in the core genome. Functional genomic analyses revealed that the marine-derived and the terrestrial strains showed differences in certain hypothetical proteins, transcriptional regulators, K+ transporter (TrK) and ABC transporters. However, species differences showed the precedence of environmental adaptation discrepancies. In each species, land specific genes were found with possible functions that likely facilitate survival in diverse terrestrial niches, while marine bacteria were enriched with genes of unknown functions and those related to transcription, phage defence, DNA recombination and repair. Conclusion: Our results indicated that the Bp isolates show distinct genomic features even as they share a common core. The marine and land isolates did not evolve independently; the transition between marine and non-marine habitats might have occurred multiple times. The lineage exhibited a priority effect over the niche in driving their dispersal. Certain intra-species niche specific genes could be related to a strain’s adaptation to its respective marine or terrestrial environment(s). In summary, this report describes the systematic evolution of 52 Bp group strains and will facilitate future studies towards understanding their ecological role and adaptation to marine and/or terrestrial environments.